The Development of Lecturer Qualifications to Voice Behavior as an Effort to Enhance Higher Education Management in Indonesia - Mulatsih, Listiana Sri; Dharma, Surya; Azliyanti, Elfitra; Putri, Nindy Yudita (International Journal of Economics Development Research (IJEDR), 2024)
The efficacy of managing higher education institutions is influenced by a multitude of factors, among which human resource management holds significant importance. Both individual and collective behaviours within the workforce play a substantial role in shaping the institution's performance. Individual workplace behaviours, which can be evaluated through levels of job satisfaction, are classified into four categories based on whether they are constructive or destructive, and active or passive. A focal point of this study is the concept of voice behaviour. Research concerning human resources within higher education often centres on performance metrics or other elements directly associated with their core responsibilities, defined under the Tri Dharma of higher education. This study encompasses all lecturers actively engaged in teaching at X University, spanning across various ranks and qualifications. Participants were grouped into several demographic categories, namely: gender, age, highest educational attainment, and academic position. The objective of this research is to characterise the constructive behaviours of lecturers and examine the variances across these demographic groups. The analytical approach employed involves analysis of variance (ANOVA) and hypothesis testing through the t-test